Prevalence, Parental Knowledge, and Factors Associated with Delayed Treatment of Testicular Hydrocele in Toddlers at Wagir Community Health Center - Anderson, Vincent Enrico; Daryanto, Besut; Nurhadi, Pradana (Brawijaya Journal of Urology, 2025)
Introduction. Testicular hydrocele is a genitourinary defect that can occur in males, either due to a lymphatic infection or congenital cause. Congenital testicular hydrocele is rarely reported in epidemiological data, both nationally and internationally. Additionally, if a hydrocele does not resolve naturally, it must be treated after the age of 1 year to prevent complications. This study aims to identify the incidence of congenital testicular hydrocele in several toddler health posts within the working area of the Wagir Community Health Centre, Malang Regency, East Java, Indonesia, assess parental knowledge, and analyze factors associated with delayed treatment. Methods. This descriptive and observational analytic study involved 248 male toddlers in 11 villages in Wagir, Malang Regency, East Java, Indonesia, utilizing questionnaires and physical examinations. Data was obtained passively through screening of villagers who came to the study site. Analysis was then conducted using the SPSS software by Pearson’s Chi-Square and Binary Logistic Regression. Results. From a total of 248 children, 4.44% were found with testicular hydrocele, with 1.21% cases experiencing delayed treatment. Poor knowledge about this condition was found in 81.82% of the sample. No relationship was found significant between the sociodemographic factors and health factors analyzed and the delay in hydrocele treatment (GLM, Wald Chi-Square, p = 1.000 > 0.05). Conclusion. The incidence rate of testicular hydroceles in toddlers under five years old at the integrative service post within the working area of Wagir Health Center of Malang Regency was 4.44%, of which 1.21% of cases experienced delays in treatment. Parents' knowledge of the incidence of testicular hydroceles in toddlers under five years old is still lacking. There was no significant relationship between the factors analyzed and the delay in testicular hydroceles management. Keywords: delay in treatment, epidemiology, sociodemographic factors, testicular hydrocele